Sudden cardiac death : report of a WHO scientific group, meeting held in Geneva from 24 to 27 October 1984 - WHO Scientific Group on Sudden Cardiac Death; World Health Organization (Geneva : World Health Organization, 1985)
Reviews accumulated data on sudden cardiac death in an effort to determine the consensus of scientific opinion on incidence, causes, predictive factors, and possibilities for prevention. Areas where future research should concentrate are also identified. The report surveys current knowledge on epidemiology, pathology, and pathogenesis, and mechanisms of the terminal event. Evidence implicating factors such as platelet-thrombus formation and sudden increases in myocardial oxygen demand is considered together with the possibility that certain types of autonomic neural activity can lead to the onset of lethal arrhythmias. Sections devoted to prediction and prevention point to the great need for more knowledge on the risk factors that are specific to sudden cardiac death, their predictive values and the possibilities of controlling them
1. Introduction -- 2. defining sudden cardiac death -- 3. Epidemiology -- 4. Pathology and pathogenesis -- 5. Mechanisms of the terminal event -- 6. The autonomic nervous system and sudden cardiac death -- 7. Disorders of the myocardium -- 8. Prediction of sudden cardiac death -- 9. Prevention of sudden cardiac death -- 10. Conclusions and recommendations -- Acknowledgements -- References
Keywords: Etiology; Mortality